THE ROLE OF SOCIAL MEDIA AND INFLUENCERS IN FORMING BEAUTY INDUSTRY TRENDS - Anel Barat (American Journals Publishing, 2025)
This article examines the role of social media and influencers in shaping beauty industry trends, with a focus on manicure and nail design. It examines the mechanisms of visual content distribution, the influence of influential bloggers and celebrities on consumer preferences, and the popularization of new styles and techniques. Particular attention is paid to practical aspects: it analyzes current trends, their promotion through social media, and their impact on the choice of colors, shapes, and nail designs. The study's findings demonstrate that social media and influencers are key factors in shaping fashion trends, facilitating the rapid adoption of innovations and their adaptation to audience preferences.
Keywords: Social media, influencers , beauty industry, nail design, manicure, trends, visual content, consumer preferences, beauty marketing, fashion trends.